An ultrasonic regulation type freeze-dried silk fibroin material, an ultrasonic regulation type freeze-dried silk fibroin microneedle and a preparation method thereof

CN122978252APending Publication Date: 2026-10-27GRANDHOPE BIOTECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611201479.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

例如,将丝素蛋白与壳聚糖共混后冷冻干燥,但冻干处理后丝素蛋白的β-折叠含量较低,所制备微针的机械强度仍不理想,且共混体系的生物安全性难以保证

Benefits of technology

本申请的超声调控型冻干丝素蛋白材料及其制备方法,对丝素蛋白溶液使用物理超声处理方法,诱导丝素蛋白发生构象转变,促进无规卷曲向β-折叠结构转化,并诱导SilkII型晶体的形成。并且将高温高压灭菌、冷冻干燥与超声物理交联技术相结合,制得可长期稳定储存的冻干丝素蛋白原料,并通过调节超声参数实现对丝素蛋白二级结构及结晶度的精准调控,获得力学强度、溶胀性能、降解行为及药物释放特性可调的丝素蛋白;制备过程绿色安全,生物相容性好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978252A_ABST
    Figure CN122978252A_ABST
Patent Text Reader

Abstract

The application provides an ultrasonic regulation type freeze-dried silk fibroin material, an ultrasonic regulation type freeze-dried silk fibroin microneedle and a preparation method thereof; a silk fibroin solution is subjected to high-temperature and high-pressure steam sterilization and freeze-drying to form a freeze-dried sponge, and after being redissolved with water, the silk fibroin is subjected to ultrasonic treatment to induce conformational transition of the silk fibroin, promote random coil to β-fold structure transformation and Silk II type crystal formation; the application combines physical ultrasonic treatment, high-temperature and high-pressure sterilization and freeze-drying to prepare freeze-dried silk fibroin which can be stored for a long time, and realizes accurate regulation of secondary structure and crystallinity of the silk fibroin through ultrasonic treatment, thereby obtaining silk fibroin microneedle with adjustable mechanical strength, swelling performance, degradation behavior and drug release characteristics; the preparation process is green and safe, and has good biocompatibility; the preparation process is simple and efficient, the operation is a mature industrial process, the equipment requirement is low, the operation process is simple, and the large-scale production can be easily realized, and the application has industrialization application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of biomedical materials technology, and particularly relates to an ultrasound-controlled freeze-dried silk fibroin material and its preparation method, and an ultrasound-controlled freeze-dried silk fibroin microneedle. Background Technology

[0002] Silk fibroin (SF) is a structural protein extracted from natural silkworm cocoons. As a natural high-molecular-weight biomaterial, silk fibroin possesses biocompatibility, biodegradability, low immunogenicity, and mechanical properties, and has been applied in biomedical fields such as wound dressings, tissue engineering scaffolds, and drug delivery carriers. The crystal structure of silk fibroin is mainly divided into two crystal forms: Silk I and Silk II. The Silk I crystal form is mainly composed of α-helices, β-turns, and random coils, exhibiting poor stability but a faster degradation rate and flexibility. The Silk II crystal form, on the other hand, is dominated by a stable β-sheet structure, providing the mechanical strength and structural stability of silk fibroin. By controlling the relative content and ratio of the two crystal forms, various properties of silk fibroin materials, such as degradation rate, mechanical properties, and swelling behavior, can be adjusted and optimized.

[0003] Microneedles (MNs) are a novel transdermal drug delivery system that uses an array of micron-sized needles to penetrate the stratum corneum of the skin, achieving painless and efficient delivery of drugs, vaccines, or active substances without irritating nerves and blood vessels in the dermis. Therefore, they combine the convenience of transdermal patches with the high efficiency of injection. The unique structural tunability of silk fibroin makes it an ideal matrix material for microneedle fabrication, and silk fibroin-based microneedles have shown promising applications in wound healing, scar repair, and diabetes treatment.

[0004] However, existing technologies for preparing silk fibroin microneedles still have many shortcomings. First, at the raw material level, liquid silk fibroin solutions have poor stability, are prone to denaturation and degradation, and are difficult to store for long periods, resulting in low preparation efficiency and significant batch-to-batch variations, thus limiting the large-scale production and application of silk fibroin materials. Second, microneedles prepared directly from freshly extracted silk fibroin solutions generally suffer from insufficient mechanical strength and high solubility, making it difficult to meet the requirements for puncture performance and controlled drug release in practical applications.

[0005] To address these issues, existing technologies often employ blending modification or cross-linking treatments. For example, silk fibroin is blended with chitosan and then freeze-dried. However, the β-sheet content of the silk fibroin is low after freeze-drying, resulting in unsatisfactory mechanical strength of the prepared microneedles, and the biocompatibility of the blended system is difficult to guarantee. Chinese invention patent CN108047466A discloses a method for chemically cross-linking silk fibroin with pentylene glycol. After cross-linking, the breaking strength of the microneedles is significantly improved. However, the introduction of the chemical cross-linking agent poses a risk of residue, which can affect the biocompatibility of silk fibroin and present potential safety risks to skin and human tissues. Furthermore, the cross-linked material is predominantly β-sheet structure, exhibiting problems such as low swelling capacity and slow drug release. In addition, some studies have used steam annealing to improve the mechanical strength of microneedles, reaching a maximum of 1.53 N / needle. However, this process is cumbersome and time-consuming, hindering large-scale production.

[0006] Therefore, how to achieve precise control of the mechanical strength, swelling properties, degradation behavior and drug release characteristics of silk fibroin microneedles through simple and green methods remains a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0007] This application provides an ultrasound-controlled freeze-dried silk fibroin material and its preparation method, as well as an ultrasound-controlled freeze-dried silk fibroin microneedles, to solve the problems existing in related technologies. The technical solution is as follows: In a first aspect, embodiments of this application provide a method for preparing ultrasound-controlled freeze-dried silk fibroin material, comprising the following steps: Silk fibroin solution was sterilized by high temperature and high pressure steam and then freeze-dried to obtain freeze-dried silk fibroin sponge; The freeze-dried silk fibroin sponge was reconstituted with water and subjected to ultrasonic treatment under ice bath conditions to obtain the ultrasonically regulated freeze-dried silk fibroin material.

[0008] In one embodiment, high-temperature and high-pressure steam sterilization is performed at 0.1 MPa and 121°C for 15-25 minutes; the freeze-drying process involves pre-freezing at -30°C to -50°C for 4-12 hours, followed by vacuum drying under frozen conditions for 24-48 hours.

[0009] In one embodiment, the reconstitution time is 30-240 min, and after dissolution, the solution is centrifuged at 5000-10000 rpm for 5-30 min. The supernatant is then taken to obtain the reconstituted silk fibroin solution. The reconstituted silk fibroin solution has a mass concentration of 3-10%.

[0010] In one embodiment, the ultrasound uses a cell ultrasonic disruptor with an ultrasonic power of 50-500W and an ultrasound time of 1-120min; the ultrasound mode is intermittent ultrasound, alternating between 3-10s ultrasound and 3-10s pause.

[0011] In one embodiment, natural silkworm cocoons are boiled in a weakly alkaline solution to degummify, washed, and dried; then dissolved in lithium bromide solution and dialyzed to obtain the silk fibroin solution.

[0012] In one embodiment, the weak alkaline solution is a mixed solution of sodium carbonate and sodium bicarbonate with a pH of 8 to 9.5; the mass ratio of sodium carbonate to sodium bicarbonate is 1:(1 to 5). The cleaning process involves washing with water 2-4 times; boiling to remove the adhesive and then repeating the cleaning process 2-4 times. Drying is carried out at 50-65℃ for 5-12 hours; The lithium bromide solution concentration was 9.3 mol / L, and the dissolution was carried out at 50~65℃; Deionized water was used as the dialysate, and the total dialysate duration was 12-36 hours. The dialysate was replaced every 1.5-2.5 hours.

[0013] Secondly, embodiments of this application provide an ultrasound-controlled freeze-dried silk fibroin material, which is prepared by the above-described method for preparing ultrasound-controlled freeze-dried silk fibroin material.

[0014] Thirdly, this application provides an ultrasound-controlled freeze-dried silk fibroin microneedle, which is prepared from the above-mentioned ultrasound-controlled freeze-dried silk fibroin material; the microneedle is conical in shape, with a height of 200~800μm and a bottom diameter of 150~500μm.

[0015] In one embodiment, a solution of ultrasound-controlled freeze-dried silk fibroin material is poured into a microneedle mold, dried after vacuum degassing, and demolded to obtain ultrasound-controlled freeze-dried silk fibroin microneedles.

[0016] In one embodiment, the mass concentration of the solution of the ultrasound-controlled freeze-dried silk fibroin material is 2-8%.

[0017] In one embodiment, the vacuum degassing conditions are 20~28℃ and -0.05MPa for 20~60 min; the drying temperature is 25~40℃ and the drying time is 2~8 h.

[0018] The advantages or beneficial effects of the above technical solutions include at least the following: This application discloses an ultrasound-controlled lyophilized silk fibroin material and its preparation method. The method involves using physical ultrasound treatment of a silk fibroin solution to induce a conformational change in the silk fibroin, promoting the transformation of random coils into β-sheet structures and inducing the formation of SilkII-type crystals. Furthermore, by combining high-temperature and high-pressure sterilization, freeze-drying, and ultrasonic physical cross-linking technology, a lyophilized silk fibroin raw material that can be stored stably for a long period is obtained. By adjusting the ultrasound parameters, the secondary structure and crystallinity of the silk fibroin can be precisely controlled, resulting in silk fibroin with adjustable mechanical strength, swelling properties, degradation behavior, and drug release characteristics. The preparation process is green, safe, and biocompatible.

[0019] The ultrasound-controlled lyophilized silk fibroin microneedles of this application possess both tunable performance and biocompatibility, showing potential applications in multiple fields such as transdermal drug delivery (especially suitable for controlled-release macromolecular drugs, protein drugs, and vaccines), biosensing, cosmetic skincare, and tissue engineering. The preparation process is simple and efficient, easily scalable; all involved operations are mature industrial processes with low equipment requirements and simple operating procedures, facilitating large-scale production and demonstrating promising industrial application prospects. The above overview is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments, and features described above, further aspects, embodiments, and features of this application will become readily apparent from the accompanying drawings and the following detailed description. Attached Figure Description

[0020] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the various drawings denote the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings depict only some embodiments disclosed in this application and should not be construed as limiting the scope of this application.

[0021] Figure 1 Scanning electron microscope (SEM) images of the internal microstructure of an untreated silk fibroin solution freeze-dried into a sponge (A) and an ice-dried silk fibroin solution freeze-dried into a sponge after high temperature and high pressure sterilization in Example 2 (B); where A1 and B1 are magnified 30 times, A2 and B2 are magnified 100 times, and A3 and B3 are magnified 300 times. Figure 2 The molecular weight distribution of the silk fibroin raw solution in Example 1 and the sterile lyophilized reconstituted solution in Example 2 is shown by gel permeation chromatography (GPC). Figure 3 The solution state diagram of ultrasound-controlled freeze-dried silk fibroin material under different ultrasound treatment times; Figure 4The average particle size of silk fibroin in the solutions of the original silk fibroin solution in Example 1, the reconstituted silk fibroin solution in Example 2, and the ultrasound-controlled freeze-dried silk fibroin materials obtained under different ultrasound treatment times is shown. Figure 5 Image of the microneedles prepared in Example 5; Figure 6 Fourier transform infrared spectrum (A), relative content of secondary structure in amide I region (C), X-ray diffraction pattern (C), and crystallinity comparison diagram (D) of microneedles prepared in Example 5, Comparative Example 1, and Comparative Example 2. Figure 7 The graph shows a comparison of the swelling rate and dissolution rate of the microneedles of Example 5 (US-SFMNs-20min), Comparative Example 1 (SFMNs), Comparative Example 2 (FD-SFMNs), Example 6 (US-SFMNs-10min), and Comparative Example 3 (US-SFMNs-30min). Figure 8 Force-displacement curves are shown for the microneedles of Example 5 (US-SFMNs-20min), Comparative Example 1 (SFMNs), Comparative Example 2 (FD-SFMNs), Example 6 (US-SFMNs-10min), and Comparative Example 3 (US-SFMNs-30min). Detailed Implementation

[0022] In the following description, only certain exemplary embodiments are briefly described. As those skilled in the art will recognize, the described embodiments can be modified in various ways without departing from the spirit or scope of this application. Therefore, the drawings and description are considered to be exemplary in nature and not restrictive.

[0023] This application provides a method for preparing ultrasound-controlled freeze-dried silk fibroin material, comprising the following steps: Silk fibroin solution was sterilized by high temperature and high pressure steam and then freeze-dried to obtain freeze-dried silk fibroin sponge; The freeze-dried silk fibroin sponge was reconstituted with water and subjected to ultrasonic treatment under ice bath conditions to obtain the ultrasonically regulated freeze-dried silk fibroin material.

[0024] Ultrasound is characterized by its ease of operation, speed, and efficiency. It can induce conformational changes in silk fibroin, promoting the transformation of random coils into β-sheet structures and inducing the formation of Silk II crystals. Under ultrasound, silk fibroin molecules undergo self-assembly and cross-linking, forming a stable internal network structure, which directly affects the mechanical strength of the material—the higher the β-sheet content, the better the mechanical properties of the silk fibroin material. Simultaneously, ultrasound treatment can also induce the silk fibroin solution to transform into a gel state, providing more possibilities for material molding and processing. As a physical treatment method, it does not require the introduction of exogenous chemical substances.

[0025] This application combines high-temperature and high-pressure sterilization, freeze-drying, and ultrasonic physical cross-linking technology to produce freeze-dried silk fibroin raw materials that can be stored stably for a long time; and through ultrasonic treatment, the secondary structure and crystallinity of silk fibroin are regulated, thereby obtaining silk fibroin with excellent mechanical strength, swelling properties, degradation behavior, and drug release characteristics.

[0026] Furthermore, the ultrasonic treatment process and the entire preparation process of this application do not require the addition of any chemical crosslinking agents, organic solvents or initiators, thus avoiding the potential toxicity risks caused by chemical reagent residues, preserving the inherent biocompatibility and biodegradability of silk fibroin, and ensuring the safety of the material for clinical application.

[0027] As one implementation method, high-temperature and high-pressure steam sterilization is carried out at 0.1 MPa and 121°C for 15-25 minutes.

[0028] High-temperature and high-pressure steam sterilization can be carried out in a high-temperature and high-pressure steam sterilizer. The silk fibroin solution is placed in the high-temperature and high-pressure steam sterilizer and sterilized at 0.1 MPa and 121℃ for 15-25 minutes. The molecular weight of the unsterilized silk fibroin solution is 500-700 kDa, and the solution is homogeneous, transparent and free of impurities. After high-temperature and high-pressure sterilization, the silk fibroin molecules undergo a certain degree of degradation, the molecular weight decreases, and the solution becomes clear and slightly yellow.

[0029] As one implementation method, the freeze-drying process involves pre-freezing at -30℃ to -50℃ for 4 to 12 hours, followed by vacuum drying under frozen conditions for 24 to 48 hours.

[0030] This invention prepares a freeze-dried sponge by sterilizing a silk fibroin solution under high temperature and high pressure. The freeze-dried sponge, when observed under a scanning electron microscope, has a regular sheet-like structure with gaps and a smooth sheet surface. In contrast, the freeze-dried sponge obtained by freeze-drying without sterilization has a disordered internal microstructure and no clear sheet-like layers.

[0031] Furthermore, the raw materials are freeze-dried after high-temperature and high-pressure sterilization, ensuring their sterility from the source and improving their long-term storage stability. They can be sealed and stored for several months in a dry, light-proof environment at 20-30℃ and 30-50% relative humidity without changing their performance, solving the problems of easy deterioration and difficult storage of liquid silk fibroin solutions. When using, they can be reconstituted as needed, with a reconstitution rate of 95-100%, minimizing raw material loss and improving ease of use and raw material utilization.

[0032] In one embodiment, the reconstitution time is 30-240 min, and after dissolution, the solution is centrifuged at 5000-10000 rpm for 5-30 min. The supernatant is then taken to obtain the reconstituted silk fibroin solution.

[0033] Purified or deionized water is used as the solvent for reconstitution, and the reconstitution rate of the lyophilized sponge is 95-100%. Therefore, reconstitution can be performed as needed, resulting in minimal raw material loss and improving ease of use and raw material utilization. After dissolution, centrifugation yields a homogeneous silk fibroin solution free of precipitates and floating matter.

[0034] In one embodiment, the mass concentration of the ultrasonically treated silk fibroin solution is 3-10% by mass.

[0035] As the ultrasound time increases, the silk fibroin solution gradually gels and becomes more concentrated. If the concentration of the silk fibroin solution is too high, the degree of gelation is difficult to adjust precisely.

[0036] As one implementation method, the ultrasound uses a cell ultrasonic disruptor with an ultrasonic power of 50~500W and an ultrasound time of 1~120min; the ultrasound mode is intermittent ultrasound, alternating between 3~10s ultrasound and 3~10s pause.

[0037] In this embodiment, the cell ultrasonic disruptor is equipped with a 6-20mm amplitude transformer. Ice bath conditions and intermittent ultrasound are used to avoid protein denaturation due to excessively high solution temperatures.

[0038] In this embodiment, by increasing the ultrasonic power or extending the ultrasonic time, the self-assembly and cross-linking of silk fibroin molecules can be promoted, increasing the relative content of β-sheet structures and the crystallinity of Silk II type crystals, thereby achieving the regulation of material properties. Therefore, the ultrasonic power of this application can be any value of 50W, 100W, 150W, 200W, 250W, 300W, 350W, 400W, 450W, and 500W, or any value between any two; the ultrasonic time can be any value of 1min, 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, and 120min, or any value between any two; preferably, after ultrasonic treatment according to this application, the silk fibroin remains in a solution state or in a hydrogel state before gelation.

[0039] In one implementation method, natural silkworm cocoons are boiled in a weakly alkaline solution to degummify, washed, and dried; then dissolved in lithium bromide solution and dialyzed to obtain the silk fibroin solution.

[0040] In one implementation method, the weak alkaline solution is a mixture of sodium carbonate and sodium bicarbonate with a pH of 8-9.5; the mass ratio of sodium carbonate to sodium bicarbonate is 1:(1-5). Sodium carbonate and sodium bicarbonate provide a weak alkaline environment, which is milder and better protects the molecular weight of silk fibroin.

[0041] As one implementation method, after boiling to remove the glue, wash with water 2-4 times. After cooling, rub with purified or deionized water three times; rubbing helps to thoroughly clean the glue strands.

[0042] As one implementation method, the boiling degumming-washing process is repeated 2 to 4 times. Through repeated boiling and washing processes, the glue between the silkworm cocoon fibers is fully removed, and the fibers are fully exposed.

[0043] In one implementation method, drying is carried out at 50-65°C for 5-12 hours. The dried silkworm cocoon fibers dissolve more readily in a lithium bromide solution. The lithium bromide solution concentration is 9.3 mol / L, and dissolution is performed at 50-65°C.

[0044] In one implementation method, the total dialysis time is 12-36 hours, with the dialysate being replaced every 1.5-2.5 hours. The dialysate is purified water or deionized water, and it is replaced every 1.5-2.5 hours during dialysis to effectively remove small molecule impurities such as lithium bromide. After dialysis, purified water or deionized water is used to adjust the concentration of the silk fibroin solution.

[0045] This application provides an ultrasound-controlled freeze-dried silk fibroin material, which is prepared by the above-described method for preparing ultrasound-controlled freeze-dried silk fibroin material.

[0046] This application provides an ultrasound-controlled freeze-dried silk fibroin microneedle, which is prepared from the aforementioned ultrasound-controlled freeze-dried silk fibroin material.

[0047] In this embodiment, a solution of ultrasound-controlled freeze-dried silk fibroin material is poured into a microneedle mold, dried after vacuum degassing, and demolded to obtain ultrasound-controlled freeze-dried silk fibroin microneedles.

[0048] The mold is made of PDMS material. The microneedle mold has a conical shape, a needle height of 200~800μm, a bottom diameter of 150~500μm, a needle tip spacing of 200~1000μm, and a square array with an array size of (10×10)~(30×30). Therefore, it is possible to prepare microneedles with a conical shape, a needle height of 200~800μm, and a bottom diameter of 150~500μm.

[0049] The mass concentration of the solution of ultrasound-controlled freeze-dried silk fibroin material is 2-8%; that is, the solution of ultrasound-controlled freeze-dried silk fibroin material with a mass concentration of 2-8% is used to prepare microneedles.

[0050] In one implementation method, vacuum degassing is performed at 20-28°C and a vacuum level ≤0.1MPa for 20-60 minutes to remove air bubbles from the solution and ensure that the solution fully fills the microneedle cavity. Drying temperature is 25-40°C, and drying time is 2-8 hours.

[0051] In one embodiment, the microneedles produced have a β-sheet content of 40%, a breaking force of 1.55 N / needle, and a dissolution rate of 4%.

[0052] The following is a further explanation using specific embodiments.

[0053] Unless otherwise specified, the experimental methods used in this application are all conventional methods; and the materials and reagents used are all commercially available unless otherwise specified.

[0054] Example 1 Natural silkworm cocoons raised in Northwest China's sericulture base were selected as raw materials. 20g of natural silkworm cocoons were weighed, cut into pieces, and placed in a deionized water solution with a pH of 9 containing 0.75g NaHCO3 and 0.25g Na2CO3. The solution was boiled for 30 minutes for degumming. The silk was then drained and washed three times with deionized water. The boiling-washing process was repeated three times to obtain pure degummed silk. The degummed silk was then placed in an oven and dried at 60℃ for 8 hours until the degummed silk fibers formed a fluffy clump. 10g of dried degummed silk and 66.65mL of 9.3M lithium bromide solution were added to a round-bottom flask and heated in a water bath at 60°C for 2 hours until the silk was completely dissolved. The solution was then filtered through a funnel with degreased cotton. The filtered silk fibroin solution was placed into a dialysis bag and dialyzed for a total of 24 hours using deionized water as the dialysis solution. The dialysis solution was replaced at 2h, 4h, 6h, 8h, and 12h. After dialysis, the pH of the original silk fibroin solution was adjusted to 6.0~7.0.

[0055] Example 2 The silk fibroin protein stock solution prepared in Example 1 was adjusted to a mass concentration of 3%, transferred to a high temperature and high pressure sterilizer, and sterilized at 121°C and 0.1 MPa for 20 min. The material was transferred to the pre-freezing chamber of a freeze dryer and pre-frozen at -20°C for 8 hours, followed by vacuum drying for 48 hours. After freeze-drying, a fluffy, sponge-like fibroin freeze-dried material (freeze-dried sponge) was obtained. Weigh out lyophilized sponge at a theoretical concentration of 8%, dissolve it in purified water for 50 min; after dissolution, centrifuge at 8000 rpm for 10 min, and take the supernatant to obtain the reconstituted silk fibroin solution; take 5 mL of the reconstituted silk fibroin solution in a vial, place the vial in an ice bath, and use an ultrasonic cell disruptor (equipped with a 6 mm diameter amplitude transformer) for ultrasonic treatment; insert the amplitude transformer about 1 cm below the liquid surface, set it to intermittent ultrasonic mode: alternating between 3 seconds of ultrasonic treatment and 3 seconds of pause; set the ultrasonic power to 100 W, and ultrasonic treatment for 20 min to obtain the solution of the ultrasonically regulated lyophilized silk fibroin material.

[0056] Example 3 The silk fibroin protein stock solution prepared in Example 1 was adjusted to a mass concentration of 3%, transferred to a high temperature and high pressure sterilizer, and sterilized at 121°C and 0.1 MPa for 20 min. The material was transferred to the pre-freezing chamber of a freeze dryer and pre-frozen at -20°C for 8 hours, followed by vacuum drying for 48 hours. After freeze-drying, a fluffy, sponge-like fibroin freeze-dried material (freeze-dried sponge) was obtained. Weigh out lyophilized sponge at a theoretical concentration of 8%, dissolve it in purified water for 50 min; after dissolution, centrifuge at 8000 rpm for 10 min, and take the supernatant to obtain the reconstituted silk fibroin solution; take 5 mL of the reconstituted silk fibroin solution in a vial, place the vial in an ice bath, and use an ultrasonic cell disruptor (equipped with a 6 mm diameter amplitude transformer) for ultrasonic treatment; insert the amplitude transformer about 1 cm below the liquid surface, set it to intermittent ultrasonic mode: alternating between 3 seconds of ultrasonic treatment and 3 seconds of pause; set the ultrasonic power to 100 W, and ultrasonic treatment for 10 min to obtain the solution of the ultrasonically regulated lyophilized silk fibroin material.

[0057] Example 4 The silk fibroin protein stock solution prepared in Example 1 was adjusted to a mass concentration of 3%, transferred to a high temperature and high pressure sterilizer, and sterilized at 121°C and 0.1 MPa for 20 min. The material was transferred to the pre-freezing chamber of a freeze dryer and pre-frozen at -20°C for 8 hours, followed by vacuum drying for 48 hours. After freeze-drying, a fluffy, sponge-like fibroin freeze-dried material (freeze-dried sponge) was obtained. Weigh out lyophilized sponge at a theoretical concentration of 8%, dissolve it in purified water for 50 min; after dissolution, centrifuge at 8000 rpm for 10 min, and take the supernatant to obtain the reconstituted silk fibroin solution; take 5 mL of the reconstituted silk fibroin solution in a vial, place the vial in an ice bath, and use an ultrasonic cell disruptor (equipped with a 6 mm diameter amplitude transformer) for ultrasonic treatment; insert the amplitude transformer about 1 cm below the liquid surface, set it to intermittent ultrasonic mode: alternating between 5 s of ultrasonic treatment and 5 s of rest; set the ultrasonic power to 100 W, and ultrasonic treatment for 5 min to obtain the solution of the ultrasonically regulated lyophilized silk fibroin material.

[0058] Performance testing of silk fibroin materials: (1) Comparison of microstructure of unsterilized and sterilized freeze-dried sponges The 3% silk fibroin raw solution prepared in Example 1 was transferred to the pre-freezing chamber of a freeze dryer and pre-frozen at -20°C for 8 hours, followed by vacuum drying for 48 hours; after freeze drying, freeze-dried sponge A was obtained. The internal microstructure of freeze-dried sponge A and freeze-dried sponge B prepared in Example 2 was observed using a scanning electron microscope (SEM) after gold sponging treatment; the microstructure was observed at magnifications of 30x, 100x, and 300x, respectively. SEM images are shown below. Figure 1 As shown, A1 and B1 are SEM images at 30x magnification, A2 and B2 at 100x magnification, and A3 and B3 at 300x magnification. like Figure 1 As shown, the unsterilized silk fibroin freeze-dried sponges (A1-A3) in Example 1 have unclear internal sheet-like structures, with disordered and overlapping planar arrangements; while the freeze-dried sponges (B1-B3) obtained after high-temperature and high-pressure sterilization in Example 2 have regular internal sheet-like structures, are loose and porous with distinct gaps, and have smooth and uniform sheet surfaces. This indicates that high-temperature and high-pressure sterilization helps improve the internal microstructure of freeze-dried sponges, making them more regular and orderly.

[0059] (2) The molecular weight distribution of the silk fibroin stock solution and the sterile lyophilized reconstituted solution from Example 1 were compared using gel permeation chromatography (GPC). 5% of the silk fibroin stock solution (SF) from Example 1 and 5% of the reconstituted silk fibroin solution (FD-SF) from Example 2 were prepared as test samples. GPC test conditions: mobile phase was 0.1M sodium sulfate, 0.1M sodium phosphate buffer (pH 6.7), flow rate was 0.5 mL / min, column temperature was 30℃, and bovine thyroglobulin and bovine hemoglobin were used as standard protein controls; the molecular weight distribution was measured as follows. Figure 2 As shown.

[0060] Figure 2 The results showed that the weight-average molecular weight of the silk fibroin stock solution in Example 1 was 598.8 kDa, and the polydispersity index (PDI) was 1.04; the weight-average molecular weight of the reconstituted silk fibroin solution in Example 2 decreased to 396.8 kDa, and the PDI was 1.17. This indicates that the high-temperature and high-pressure sterilization treatment in Example 2 caused a certain degree of degradation of the silk fibroin molecules, resulting in a reduction in molecular weight. After lyophilization and reconstitution, the molecular weight distribution remained relatively narrow.

[0061] (3) The ultrasonic time in Example 2 was changed, and the ultrasonic power was set to 100W. Treatments were performed for 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, and 40 min, respectively, and the changes in solution state were observed. The results are as follows: Figure 3 As shown.

[0062] from Figure 3 The changes in the solution show that, with the extension of ultrasonic treatment time, the solution of the ultrasonic-regulated freeze-dried silk fibroin material gradually transforms from a clear and transparent state to a translucent gel state. During ultrasonic treatment of 5–20 min, the solution remains fluid but its viscosity gradually increases. After ultrasonic treatment for more than 30 min, the solution begins to show a clear tendency to gel. By 40 min, the solution has essentially lost its fluidity, forming an opaque hydrogel. Therefore, ultrasonic treatment can effectively induce the self-assembly and cross-linking of silk fibroin molecules, and the degree of cross-linking can be controlled by the ultrasonic treatment time.

[0063] (4) Particle size variation 8% of the original silk fibroin solution (SF) from Example 1, 8% of the reconstituted silk fibroin solution (FD-SF) from Example 2, and silk fibroin solutions subjected to ultrasonic treatment according to Example 2: ultrasonicated at 100W power for 10 min, 20 min, and 30 min respectively (denoted as US-10min, US-20min, and US-30min). The particle size analyzer was used for dynamic light scattering (DLS). Before the test, the cuvette was rinsed twice with the sample, the sample was added to 2 / 3 of the mark, the outer wall of the cuvette was wiped dry with lens paper and then placed in the sample cell.

[0064] Test parameter settings: Dispersion medium was water, test temperature was constant at 25℃, delay time was 50μs, and photon count was controlled between 20 and 50; data were recorded after the test curve stabilized, and each sample was tested three times to ensure the reliability of the results; results are as follows. Figure 4 As shown.

[0065] Figure 4 In the original silk fibroin solution (8% of Example 1), the average particle size was 416 nm. After sterilization, lyophilization, and reconstitution, the particle size decreased to 270 nm. After ultrasonic treatment, the particle size gradually increased with increasing ultrasonic time. During ultrasonication for 10-20 min, the particle size increased by approximately 150 nm; during ultrasonication for 20-30 min, the increase in particle size slowed down, but remained close to the particle size level of the original solution. The result of increased particle size due to ultrasonic treatment indicates that ultrasonic treatment induces physical self-assembly and cross-linking of silk fibroin molecules, increasing the number of β-sheet structures and causing aggregation. The higher the degree of cross-linking, the larger the aggregate particle size. This result is consistent with... Figure 3 The observed trends in solution state changes were consistent, further validating the regulatory effect of ultrasound on the structure of silk fibroin.

[0066] Example 5 Microneedles were prepared using a PDMS microneedle mold with a conical needle shape, a bottom diameter of 350 μm, a needle height of 550 μm, and a 20×20 well array. Microneedles were also prepared using a solution of the ultrasonically regulated lyophilized silk fibroin material prepared in Example 2. 200 μL of silk fibroin solution was injected into the mold for each group. The mold was then connected to a vacuum pump and evacuated for 30 min. After vacuum degassing, the PDMS mold was placed in a drying oven for 8 hours to allow the microneedles to fully solidify. After drying, the mold was gently demolded to obtain the silk fibroin microneedles. The prepared microneedles were conical in shape, with a base diameter of approximately 350 μm and a height of approximately 550 μm. Figure 5 As shown.

[0067] Example 6 Microneedles were prepared using a PDMS microneedle mold with a conical needle shape, a bottom diameter of 350 μm, a needle height of 550 μm, and a 20×20 well array, and a solution of the ultrasonically regulated lyophilized silk fibroin material prepared in Example 3. 200 μL of silk fibroin solution was injected into the mold for each group. The mold was then connected to a vacuum pump and evacuated for 30 min. After vacuum degassing, the PDMS mold was placed in a drying oven and dried for 8 hours to allow the microneedles to fully form. After drying, the mold was gently demolded to obtain silk fibroin microneedles. The prepared microneedles were conical in shape, with a base diameter of approximately 350 μm and a height of approximately 550 μm.

[0068] Example 7 Microneedles were prepared using a PDMS microneedle mold with a conical needle shape, a bottom diameter of 350 μm, a needle height of 550 μm, and a 20×20 well array, and a solution of the ultrasonically regulated lyophilized silk fibroin material prepared in Example 4. 200 μL of silk fibroin solution was injected into the mold for each group. The mold was then connected to a vacuum pump and evacuated for 30 min. After vacuum degassing, the PDMS mold was placed in a drying oven for 5 hours to allow the microneedles to fully form. After drying, the mold was gently demolded to obtain silk fibroin microneedles. The prepared microneedles were conical in shape, with a base diameter of approximately 350 μm and a height of approximately 550 μm.

[0069] Comparative Example 1 The difference between Comparative Example 1 and Example 5 is that the microneedles were prepared using the 8% silk fibroin protein stock solution prepared in Example 1, while the rest were the same as in Example 5.

[0070] Comparative Example 2 The difference between Comparative Example 2 and Example 5 is that the microneedles were prepared using the 8% reconstituted silk fibroin solution (without sonication) prepared in Example 2, while the rest was the same as in Example 4.

[0071] Comparative Example 3 The difference between Comparative Example 3 and Example 5 is that the solution of the ultrasound-controlled freeze-dried silk fibroin material used in Comparative Example 4 was prepared by sonicating the 8% reconstituted silk fibroin solution from Example 2 at 100W for 30 minutes, while the rest was the same as in Example 5.

[0072] Microneedle performance testing: (1) The microneedles prepared in Example 5 (US-SFMNs-20min), Comparative Example 1 (SFMNs) and Comparative Example 2 (FD-SFMNs) were ground into powder and dried to constant weight. The structure was characterized by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD), respectively. Infrared spectroscopy was performed in ATR mode, with a scanning range of 500–4000 cm⁻¹. - ¹. The infrared spectra were Gaussian smoothed and Fourier deconvolutioned using OMNIC and Origin software, and the amide I region (1600~1700 cm⁻¹) was calculated. - ¹) Relative content of secondary structures; infrared spectrum as follows Figure 6 As shown in Figure A, the relative content of secondary structures is Figure 6 As shown in B.

[0073] X-ray diffraction testing conditions: Cu target, tube voltage 40 kV, 2θ scan range 5–45°, scan speed 10° / min. Crystallinity of each sample was calculated using MDI Jade software; X-ray diffraction spectra are as follows. Figure 6 As shown in Figure C, the calculated crystallinity is as follows: Figure 6As shown in D.

[0074] from Figure 6 The results show that the microneedles in Example 5, Comparative Example 1, and Comparative Example 2 all exhibit a predominantly β-sheet structure. Specifically, the microneedles prepared by ultrasonic treatment in Example 5 (US-SFMNs-20min) had a β-sheet content of 40%, which is approximately 7 percentage points higher than the unultrasonicated lyophilized microneedles (FD-SFMNs) in Comparative Example 2. XRD results indicate that the content of both Silk I and Silk II crystals in the microneedles increased after ultrasonic treatment, resulting in a significant improvement in overall crystallinity. Therefore, ultrasonic treatment can effectively promote the self-assembly and cross-linking of β-sheets in silk fibroin, increasing the crystal content and forming a more stable internal network structure, which provides a structural basis for improving the mechanical properties of the microneedles.

[0075] (2) Swelling and loss rate Microneedles from Example 5 (US-SFMNs-20min), Comparative Example 1 (SFMNs), Comparative Example 2 (FD-SFMNs), Example 6 (US-SFMNs-10min), and Comparative Example 3 (US-SFMNs-30min) were taken respectively, and their initial weights W0 were recorded after precise weighing. Each microneedle sample was placed in a 10 mL centrifuge tube, and 5 mL of PBS buffer solution (pH=7.4) was added to completely submerge it. The tubes were then incubated in a 37°C constant temperature shaking incubator at a shaking speed of 100 rpm. After soaking for 24 hours, remove the microneedles, gently pick them out with tweezers, rinse the surface with deionized water to remove any adhering substances, and carefully blot the surface moisture with filter paper. Weigh the microneedles to obtain the weight W1 after swelling. Finally, place the microneedles in a 60℃ oven to dry to constant weight and weigh them to obtain the weight W2 after drying. The swelling ratio and solubility loss rate are calculated using the following formula: Swelling rate (%) = (W1 – W0) / W0 × 100%; Dissolution rate (%) = (W0 – W2) / W0 × 100%; The results are as follows Figure 7 As shown.

[0076] Figure 7Compared to the microneedles (SFMNs) of Comparative Example 1, the microneedles (FD-SFMNs) of Comparative Example 2 showed an increase in swelling rate of approximately 32% and a dissolution rate approaching 50%. However, after ultrasonic treatment, the swelling rate and dissolution rate of the microneedles (US-SFMNs-20 min) of Example 5 were significantly reduced. Specifically, the dissolution rate of the microneedles (US-SFMNs-10 min) of Example 6 was 18.6%, and the dissolution rate of the microneedles (US-SFMNs-30 min) of Comparative Example 3 was 4%. Therefore, the increased β-sheet cross-linking and crystallinity induced by ultrasound can, on the one hand, inhibit excessive swelling of the microneedles in a short time, and on the other hand, limit the dissolution of the microneedle matrix, thereby reducing the dissolution rate. Higher Silk II crystal content results in better structural stability of the microneedles and lower degrees of swelling and dissolution. This characteristic is significant for microneedle applications requiring retention in the skin for a certain period to achieve sustained-release drug delivery.

[0077] (3) Mechanical properties of microneedles The mechanical properties of the microneedles were tested using a texture analyzer, taking microneedles from Example 5 (US-SFMNs-20min), Comparative Example 1 (SFMNs), Comparative Example 2 (FD-SFMNs), Example 6 (US-SFMNs-10min), and Comparative Example 3 (US-SFMNs-30min).

[0078] Before testing, the texture analyzer was calibrated for weight and height. A cylindrical probe with a diameter of 2 mm (capable of simultaneously covering approximately 10 needle tips) was selected. The testing mode was set to compression mode, with a trigger force of 1 g, a testing speed of 0.1 mm / s, and a strain of 90.0%. The force-displacement curve was recorded, and the maximum force at which the microneedle broke was read and converted into the breaking force of a single microneedle. The results are as follows: Figure 8 As shown.

[0079] The breaking force of the microneedles (SFMNs) in Comparative Example 1 was 0.59 N / needle, and the breaking force of the microneedles (FD-SFMNs) in Comparative Example 2 was 0.36 N / needle. After ultrasonic treatment, the mechanical strength of the microneedles (US-SFMNs-20min) in Example 5 was significantly improved. The breaking forces of the microneedles (US-SFMNs-10min) in Example 6 prepared by ultrasonication for 10 min and the microneedles (US-SFMNs-20min) in Example 5 prepared by ultrasonication for 20 min were significantly higher than those of the microneedles (SFMNs) in Comparative Example 1. The breaking force of the microneedles (US-SFMNs-20min) in Example 5 prepared by ultrasonication for 20 min reached 1.55 N / needle, which is 2.6 times that of the original solution microneedles.

[0080] In summary, this application describes a method for obtaining ultrasound-regulated lyophilized silk fibroin material by sterilizing a silk fibroin solution under high temperature and pressure, freeze-drying, reconstituted, and then ultrasonically treating it under ice bath conditions. Physical ultrasound is used to rapidly induce a conformational change in silk fibroin molecules in situ, promoting the transformation of random coils into β-sheet structures. The preparation process is green and safe with good biocompatibility; the prepared product can be stored stably for a long time and is convenient to use. The resulting lyophilized microneedles exhibit excellent mechanical strength, swelling behavior, and drug release characteristics after loading. The overall process is simple, efficient, and easy to scale up for production.

[0081] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of those different embodiments or examples.

[0082] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "a plurality of" means two or more, unless otherwise explicitly specified.

[0083] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any person skilled in the art can easily conceive of various variations or substitutions within the technical scope disclosed in this application, and these should all be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A method for preparing ultrasound-controlled freeze-dried silk fibroin material, characterized in that, Includes the following steps: Silk fibroin solution was sterilized by high temperature and high pressure steam and then freeze-dried to obtain freeze-dried silk fibroin sponge; The freeze-dried silk fibroin sponge was reconstituted with water and subjected to ultrasonic treatment under ice bath conditions to obtain the ultrasonically regulated freeze-dried silk fibroin material.

2. The method for preparing ultrasound-controlled freeze-dried silk fibroin material according to claim 1, characterized in that, High-temperature and high-pressure steam sterilization is performed at 0.1 MPa and 121℃ for 15-25 minutes; the freeze-drying process involves pre-freezing at -30℃ to -50℃ for 4-12 hours, followed by vacuum drying under frozen conditions for 24-48 hours.

3. The method for preparing ultrasound-controlled freeze-dried silk fibroin material according to claim 1, characterized in that, The reconstitution time is 30~240min. After dissolution, centrifuge at 5000~10000rpm for 5~30min and take the supernatant to obtain the reconstituted silk fibroin solution. The reconstituted silk fibroin solution has a mass concentration of 3-10%.

4. The method for preparing ultrasound-controlled freeze-dried silk fibroin material according to claim 1, characterized in that, The ultrasound was performed using a cell ultrasonic disruptor with an ultrasonic power of 50-500W and an ultrasound time of 1-120 minutes. The ultrasound mode was intermittent, alternating between 3-10 seconds of ultrasound and 3-10 seconds of pause.

5. The method for preparing ultrasound-controlled freeze-dried silk fibroin material according to claim 1, characterized in that, Natural silkworm cocoons are boiled in a weakly alkaline solution to degummify, washed, and dried; then dissolved in lithium bromide solution and dialyzed to obtain the silk fibroin solution.

6. The method for preparing ultrasound-controlled lyophilized silk fibroin material according to claim 5, characterized in that, The weak alkaline solution is a mixture of sodium carbonate and sodium bicarbonate with a pH of 8-9.5; the mass ratio of sodium carbonate to sodium bicarbonate is 1:(1-5). The cleaning process involves washing with water 2-4 times; boiling to remove the adhesive and then repeating the cleaning process 2-4 times. Drying is carried out at 50-65℃ for 5-12 hours; The lithium bromide solution concentration was 9.3 mol / L, and the dissolution was carried out at 50~65℃; Deionized water was used as the dialysate, and the total dialysate duration was 12-36 hours. The dialysate was replaced every 1.5-2.5 hours.

7. An ultrasound-controlled freeze-dried silk fibroin material, characterized in that, It is prepared by the method for preparing ultrasound-controlled freeze-dried silk fibroin material according to any one of claims 1 to 6.

8. An ultrasound-controlled lyophilized silk fibroin microneedle, characterized in that, The microneedles are prepared from the ultrasound-controlled freeze-dried silk fibroin material as described in claim 7; the microneedles are conical in shape, with a height of 200-800 μm and a bottom diameter of 150-500 μm.

9. The ultrasound-controlled lyophilized silk fibroin microneedles according to claim 8, characterized in that, The solution of the ultrasound-controlled freeze-dried silk fibroin material as described in claim 7 is poured into a microneedle mold, dried after vacuum degassing, and demolded to obtain the ultrasound-controlled freeze-dried silk fibroin microneedles.

10. The ultrasound-controlled lyophilized silk fibroin microneedles according to claim 9, characterized in that, The mass concentration of the solution for ultrasound-controlled lyophilized silk fibroin material is 2-8%. The vacuum degassing conditions are 20~28℃ and vacuum degree ≤0.1MPa for 20~60min; the drying temperature is 25~40℃ and the drying time is 2~8h.

Citation Information

Patent Citations

  • Silk microneedle and preparation method thereof

    CN108047466A